Peningkatan Keterampilan Menyimak Dalam Mengapresiasi Drama Kearifan Lokal Melalui Metode Apresiasi Empatik Siswa Kelas XI MIA SMAS PGRI Maros - Riki Ardiansyah; Haslinda Haslinda; Rahmatiah Rahmatiah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to describe and improve listening skills in appreciating the drama of local wisdom through empathic appreciation method in Class XI MIA SMAS PGRI Maros. This study is a class action study involving one class. The subjects of this study were students of Class XI MIA SMAS PGRI Maros consisting of 20 students. Data collection techniques used in this study are tests and observations. Data collection is done by applying a learning model of empathic appreciation at the end of each cycle. Observations were made each learning process using a test of learning outcomes after learning by applying the empathic appreciation learning model took place with the perception responses of students of Class XI MIA SMAS PGRI Maros about the application of the empathic appreciation learning model. The collected Data were analyzed quantitatively and qualitatively. The results showed that with the application of empathic appreciation learning model can improve learning outcomes appreciating drama students of Class XI MIA SMAS PGRI Maros. This is evident from the increase in student learning outcomes. The research carried out obtained (1) student learning outcomes in the first cycle are in the low category of 20 students, only 7 students (35%) who get grades above KKM, while students who get grades below KKM or incomplete are 13 people (65%). Student learning outcomes in the second cycle of 20 students, there are no students (0%) Who Get grades below KKM or incomplete, and students who get grades above KKM or complete are 20 people (100%). (2) the results of the analysis show that there are changes in the attitude of students during the learning process in accordance with the results of observations of students in the first cycle is still less able to accept the material and less able to appreciate the drama, in the second cycle of students already understand well, and able to appreciate the drama according to assessment standards.